Implementation of the Learning Community Program Using the Context, Input, Process, and Product Model to Improve Student Learning Outcomes - Sabarullah, Iman; Abdulhajar, Encik; Zaitun; Irawan, Dody (Raja Zulkarnain Education Foundation, 2025)
The Learning Community Program is part of the Merdeka Curriculum strategy that aims to improve teacher competency and performance through collaboration, reflection, and continuous professional development. The Learning Community Program at SMAN 1 Teluk Bintan is named Kombel Keren (Collaborative, Educational, Responsive, and Energetic). This study aims to: 1) explore the implementation of the Learning Community Program using a descriptive evaluative approach with the CIPP (Context, Input, Process, Product) model at SMAN 1 Teluk Bintan; 2) the magnitude of the increase in teacher competency and performance; 3) the magnitude of the increase in student learning outcomes. This library research uses data from the 2020/2021 and 2024/2025 academic years. The subjects of this study were teachers of SMAN 1 Teluk Bintan. Data on the Learning Community Program were collected using documentation techniques, observation guidelines, and portfolios. Data on teacher competency and performance were collected using test instruments and documentation techniques. Data on learning outcomes were collected using documentation techniques. Implementation data were analyzed qualitatively and thematically. Data on improving teacher competency and performance as well as data on improving student learning outcomes were analyzed using descriptive statistics, namely the mean. The results of the study: 1) the implementation of the Learning Community Program used a descriptive evaluative approach with the CIPP (Context, Input, Process, Product) model based on in-house training and workshops categorized as very active; 2) the magnitude of the score for improving teacher competency and performance was between 10-20; 3) the magnitude of the increase in student learning outcomes was between 0.51 to 0.97.